Barriers to Energy Access in the Urban Poor Areas of Dhaka, Bangladesh: Analysis of Present Situation and Recommendations - Lipu, Molla Shahadat Hossain; Jamal, Taskin; Miah, Muhammad Ahad Rahman (International Journal of Energy Economics and Policy, 2013)
Energy is a crucial input to promote socioeconomic development. In Bangladesh, about 96 million people (59%) do not have access to electricity and 143 million people (88%) still depend on biomass for cooking. The urban poor living in slum areas with lack of access to clean and modern sources of energy have not been addressed comprehensively. The main objective of this study is to identify the barriers faced by the urban poor in the slum areas of Dhaka in accessing different fuels and provide specific recommendations to overcome the barriers to enable energy access. The study is mainly based on field survey covering 185 households of the four major slum areas of Dhaka, literature review, and stakeholder interviews. Many barriers have been identified through this research where urban poor face problems in accessing legal energy services due to illegal settlement, lack of explicit policy on energy and housing, lack of dedicated institution, the pervasive role of Mastaans, poor infrastructure and lack of monitoring and evaluating system. Barriers specific recommendations are also suggested based on the experiences from the field visit and the best practices outside Bangladesh are also identified. Keywords: Urban poor; Energy access; Energy policy; Slums; Dhaka JEL Classifications: C83; G28; R28